ENHANCEMENT OF SURFACE CHARACTERISTICS AND TRIBOLOGICAL PERFORMANCE OF WAAM AL6063 VIA LASER SHOCK PEENING - G., Amarnath; B, Santosh Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The rising demand for Wire Arc Additive Manufacturing (WAAM) underscores its potential as an effective alternative to conventional subtractive manufacturing methods. However, WAAM faces challenges, notably uncontrolled grain size and tensile residual stresses in fabricated components, which can limit its applications. To address these challenges, this study explores Laser Shock Peening (LSP) as an advanced post-processing technique to enhance component durability through severe plastic deformation and improved surface properties. WAAM was employed to fabricate Al-6063 alloy components, which were subsequently treated with LSP to investigate its effects on surface characteristics and tribological behavior. The LSP treatment resulted in significant improvements, including grain refinement and the formation of a high density of dislocation lines on the shock-peened surface, leading to increased surface hardness. Moreover, LSP transformed the initial tensile residual stresses into a compressive state, further enhancing the material’s performance. This study demonstrates the potential of LSP to improve the surface integrity and durability of WAAM-fabricated Al-6063 components.